Acta Martyrum from the era of persecution as one of the sources for learning about the history of the Balkans - Malinowski, Andrzej (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes the Acta Martyrum as a source for the study of the history of the Balkans during the period of Christian persecutions. The research problem concerns the value of these texts for reconstructing historical realities and their reliability. The aim of the work is to present the nature of martyrological documents and their importance for studies on the history of the region. The author applies analysis and classification of written sources. The most important results indicate that martyrological texts are divided into three groups: court records (acta), accounts of martyrdom (passiones), and legends. The first two types are particularly valuable because they contain information about the course of trials, the structure of Roman administration, and the realities of persecutions. The author also discusses the persecutions under Diocletian, indicating their scale and political significance. The conclusion is that the Acta Martyrum should be regarded as an important, although requiring critical analysis, historical source.